A descriptive analysis of anglicisms used in Ecuadorian newspapers - León Barreto, Maria Auxiliadora (2011)
The quantitative and qualitative methods were used to carry out this study, which provides a linguistic and comparative analysis of the anglicisms found. This study demonstrates that General Interest Magazines use more anglicisms, this represents almost 50%.